Gendering the condemned? : women and capital punishment in Ireland post-1922 - Black, Lynsey Catherine (Trinity College (Dublin, Ireland). School of Law, 2016)
This thesis explores the cases of the 25 women sentenced to death in Ireland post-1922. It represents the first research focusing exclusively on women and capital punishment in Ireland, and examines how the death-sentenced women were discursively constructed by the criminal justice system. Through comprehensive archival research, the thesis engages in an analysis of the cases, exploring how the individual women were constructed according to themes of infanticide, mercy, confinement, pathology, and appropriate femininity. This analysis seeks to identify the prevailing discourses which informed understandings of the condemned women, and in turn situates the cases within the broader historical context of the punishment and control of women in Ireland. The individual cases are analysed within the social and cultural context of Irish society, and of women’s place in that society; it is argued that their cases can therefore be read as markers of their place and time. The thesis examines the gendering processes at work in the construction of the condemned women, and how these informed the criminal justice responses in their cases. The thesis thus offers a gendered analysis of the death penalty in Ireland. Through this analysis, along with themes of class and rurality, tropes of domesticity, motherhood, respectability, sexuality, masculinity and pathology emerge. It is argued that these themes are influenced by, and indicative of, a particularly Irish form of paternalism rooted in the patriarchal society of the time. This paternalism, understood as representing the protections afforded to women as a ‘class’ of persons premised on their inferior status, is evident in the differential treatment of the women herein by the criminal justice system. All but one of the 25 women had their sentences commuted; many were confined for lengthy periods in semi-penal sites; ‘mercy’ was therefore extended to them in a way which often led to a particularly punitive outcome. The exercise of paternalism meant that those women sentenced to death in post-Independence Ireland were punished differently, punished severely, and punished as women.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin, 2016